Single-stage surgery experience in a case of coarctation of the aorta with an arch aneurysm combined with severe coronary artery disease - Mo, Ran; Yan, Yiguang; Wang, Dongjin (Journal of Thoracic Disease, 2017)
The best surgical approach for coarctation of the aorta (COA) combined with other cardiac diseases is uncertain. The simultaneous intracardiac repair of complex pathologies is desirable because multistage procedures may lead to a higher rate of mortality. We describe a case involving a 61-year-old woman who was suffering from COA with a concomitant arch aneurysm and coronary artery disease. We managed her case via single-stage surgery that included a median sternotomy.